Scaphoid Fractures below the Age of 10: Case Series and Review of the Literature - Tataria, Rachana; Ting, Jeannette; Jester, Andrea; Lindau, Tommy R.; Oestreich, Kerstin (Journal of Wrist Surgery, 2020)
Background Scaphoid fractures are relatively uncommon in children, especially below the age of 10 due to the ossification of the scaphoid bone, which starts around 4 to 6 years of age and continues until 13 to 15 years of age, where pediatric scaphoid fractures peak. This makes the diagnoses challenging in this age group.Methods The primary aim of this study was to analyze prospectively collected data in managing scaphoid fractures. All cases in children up to the age of 10 years, treated in a tertiary pediatric hand and upper limb from January 2014 to June 2018 were included. Parameters studied were patient demographics, clinical presentation, mechanism of injury, investigations, type of fracture, associated injuries, treatment offered, outcomes and complications. The secondary aim was to review the literature due to the limited knowledge about these fractures in these low age groups.Results A total of 23 patients with documented scaphoid fractures in children up to the age of 10 years were found. Final diagnosis in all these patients was done with magnetic resonance imaging (MRI). The mean age was 9.8 years, with female preponderance. Scaphoid waist was the most common location. Five patients had associated fractures of the capitate and one patient had associated second metacarpal base fracture. All patients were managed nonoperatively. The average time of immobilization was 6.6 weeks (range: 4–10 weeks). A majority of patients had minor symptoms after the fracture, most likely due to the immobilization time.Conclusion Scaphoid fractures are rare in the pediatric population up to the age of 10. MRI is most often needed to confirm diagnosis. Nonoperative management of most scaphoid fractures in this age group is safe and feasible with no significant long-term morbidity. Surgical management of scaphoid fractures might be required in very selected cases.Level of Evidence This is a Level IV study.
Keywords: scaphoid; fracture; pediatric; children